On Gaussian nonlinear transformations - Ganikhodjaev, Nasir; Hamzah, Nur Zatul Akmar (American Institute of Physics, 2015)
In this paper, we construct the family of Gaussian non-linear transformations defined on the continual sample space of real numbers R and investigate their trajectory behaviors.